计算:(x的平方-x-4)(3x+1)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/09 01:15:11
计算:(x的平方-x-4)(3x+1)计算:(x的平方-x-4)(3x+1)计算:(x的平方-x-4)(3x+1)=x²×3x+x²×1-x×3x-x×1-4×3x-4×1=3x&
计算:(x的平方-x-4)(3x+1)
计算:(x的平方-x-4)(3x+1)
计算:(x的平方-x-4)(3x+1)
=x²×3x+x²×1-x×3x-x×1-4×3x-4×1
=3x³+x²-3x²-x-12x-4
=3x³-2x²-13x-4
计算:(x的平方-x-4)(3x+1)
计算(x-1)(x的平方-4x+3)-x(x的平方-5x+2)
计算 【(x+1)分之(x-1)-(x+2)分之(x+1)】/(x的平方+4x+4)分之(x+3)
计算2(x的平方-x+1)-(-2x+3x的平方)+(1-x)
(x+3)的平方-(x-1)(x-2)计算
计算;{4(x)的平方-(9分之4x)+1}{-3(x)的平方}
(x-6)(x的平方+x+1)-x(2x+1)(3x-1)计算
计算:(x的平方-1)(x+1)-(x的平方-2)(x-4)
(x的平方-7x-2)-(-2x的平方+4x-1) 计算
计算.3x平方+{2X平方-3X}-{-X+5X的平方} 其中X=314 {5XY-8X平方}-{-12X平方+4XY} 其中X=-2分之1,Y=2
计算x的平方+2x+3
计算3/X-6/1-X-X+5/X的平方-X
计算(x+1)(x-3)-(x+2)的平方+(x+2)(x-2)
计算(x+1)(x-3)-(x+2)的平方+(x+2)(x-2)
数学计算(9x平方-6x+1)÷(x-2)×(2x-(x)的平方)÷(3x-1)
计算(2x+3)(2x-3)-4x(x-1)+(x-2)的平方
x(x的平方-2x+1)-3x(x的平方-4x+1)
(x-2)的平方+4(x-1)的计算过程